ANALISIS PERANAN ROOM ATTENDANT DALAM MENINGKATKAN KUALITAS PELAYAN DI DE BRAGA BY ARTOTEL - Rifky Surya; Sti Zakiah (Media Bina Ilmiah, 2025)
The housekeeping department plays an important role in maintaining the quality of hotel services, especially in terms of cleanliness, comfort, and tidiness of facilities. This study aims to analyze the role of room attendants in improving the quality of service at the De Braga Hotel by Artotel. The study was conducted using a quantitative method involving questionnaires to hotel guests and housekeeping staff to identify the problems faced.The results showed that housekeeping performance significantly influenced the level of guest satisfaction, with factors such as punctuality, cleaning quality, and staff friendliness being the main aspects appreciated by guests. Operational constraints such as shortages of manpower and limited work tools were identified as major obstacles to achieving effectiveness.This study concluded that improving training, resource management, and utilization of technology can support better housekeeping performance. Practical recommendations are provided to improve housekeeping operational standards, so that hotels can continue to maintain and improve guest satisfaction levels.